Exploring the Role of Online 'Ojek' In Public Transport Trips: Case of Jakarta Metropolitan Area Rail Users. (May 2018) - Saffan, A F; Rizki, M
Abstract: The invention of information technology shapes people's lives in the city, including the recent invention of online motorcycle taxi service. Known as 'ojek', it offers a reliable means of tactical commuting in dealing with traffic congestion in Greater Jakarta. Moreover, recent development in the online system improves the punctuality and reliability of ojek services. The emergence disrupts the transport landscape, resulting in commuters' dependency to this transport mode. However, academic sources are insufficient to answer the policy debate among planners and policy maker regarding this issue. This paper probes the role of online ojek in Jakarta Metropolitan Area Rail users' trip from their perspective, especially for the first mile and the last mile of their trip. The intensive commuter survey is currently being done at selected stations to gain information of their first mile and last mile trip diary. Discriminant analysis will be exercised to explain that to some extent online ojek is able to work to fill the gap produced due to minimum proper pedestrian facilities and a lack of public transport connection.